المنهج البياني عند الإمام الزمخشري في الكشاف: دراسة تحليلية لسورة ‏الفرقان - Mardhiah binti Ahmad Sahimi
This research aims to discuss the appearance of the inimitable Qur'anic eloquence, which was used by Imam al-Zamakhshari as a methodology of interpreting the Qur'an. It seeks to identify the concepts, types and benefits of this method. The necessity of this research lies on revealing the aspects of eloquence which is compatible between holy verses and its meaning, and the accurate consistency in the connotations and context of holy verses. The study depends on inductive method in reviewing the Qur'anic verses of Surah al-Furqan and referring to all bibliography of languages and exegesis covering the ancient and modern books. It also utilizes the analytical method to discover the aspects of inimitable eloquence and tries to derive it in interpretation of Surah al-Furqan. The researcher has reached some results through this study. The most important results are the discovery of the rhetorical method in the effort of Imam al-Zamakhshari in the interpretation and understanding of the Qur'anic verses as shown in Surah al-Furqan. This Surah also reveals that its verses hold a variety of rhetorical modes from the sciences of semantics and syntax that takes into account the context between words and its meaning, and exigencies of the situation such as adjectives, anastrophe, general and restrictive, non-figurativeness and trope. These two sciences had been used in conquering his ideology of al-Mu'tazilah which can be found during his interpretation of verses that are related to the style of metaphor in this surah.